Web dynpro ABAP for practitioners - Gellert, Ulrich; Cristea, Ana Daniela (Springer Berlin Heidelberg, 2013)
Web Dynpro ABAP, a NetWeaver web application user interface tool from SAP, enables web programming connected to SAP Systems. The authors' main focus was to create a book based on their own practical experience. Each chapter includes examples which lead through the content step-by-step and enable the reader to gradually explore and grasp the Web Dynpro ABAP process. The authors explain in particular how to design Web Dynpro components, the data binding and interface methods, and the view controller methods. They also describe the other SAP NetWeaver Elements (ABAP Dictionary, Authorization) and the integration of the Web Dynpro Application into the SAP NetWeaver Portal. The new edition has been expanded to include chapters on subjects such as POWER Lists; creating the Modal Windows and External Windows; using Web Dynpro application parameters and Shared Objects to communicate between the Web Dynpro ABAP Application and Business Server Pages; and creating multi-language mails using Web Dynpro ABAP.